Political Resolutions in the International Labor Organization: The Experience since 1964 - Tajgman, David (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1981)
This paper examines the difficulty in defining a "political resolution"; it analyzes the increased use of political resolutions in the ILO, and discusses various attempts made to restrain their use and minimize their disruptive influence.